Aedes (Stegomyia) albopictus in rural areas in Brazil: First Record in the State of Ceara - Estelita Lima Cândido; Ulisses Mariano da Silva; Angélica Rodrigues de Souza Costa; Elayne Eally Silva de Oliveira Morais; Gledson Micael da Silva Leite; Carlos Wagner Oliveira (Global Journal of Ecology - Peertechz Publications, 2023)
Background: This work aims to describe the finding of Aedes albopictus in an intra- and peridomiciliary area of the rural area in the south-central region of Ceará and discuss the need for entomological surveillance of this species in the country.  Method: Through traps installed in an intra- and peridomiciliary environment and artificial breeding grounds, eggs and larvae of Ae. albopictus were captured in a rural area of the state of Ceará.  Results: This is the first record of Ae. albopictus in the south-central region of the state of Ceará. We collected 418 eggs and 252 larvae from Ae. albopictus, being 85% of eggs in the peridomiciliary area, on average 29.41 (± 37.34) eggs per trap. As for larvae, about 70% of them were caught on tires. Only 42 larvae (14,2%) belonged to species other than the genus Aedes, found in tires and an engine.  Conclusion: The presence of Ae. albopictus in rural areas close to urban areas warns of the need to effectively insert this vector as a surveillance target, carry out an active search, monitor its presence in municipalities, and investigate its involvement with outbreaks in or near areas where they are present.